The reproductive biology of two small southern African mammals, the spiny mouse, Acomys spinosissimus (Rodentia: Muridae) and the Eastern rock elephant-shrew, Elephantulus myurus (Macroscelidea: Macroscelididae) - Chimimba, Christian Timothy (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.